2019
DOI: 10.3390/polym11111899
|View full text |Cite
|
Sign up to set email alerts
|

Continuous, Strong, Porous Silk Firoin-Based Aerogel Fibers toward Textile Thermal Insulation

Abstract: Aerogel fiber, with the characteristics of ultra-low density, ultra-high porosity, and high specific surface area, is the most potential candidate for manufacturing wearable thermal insulation material. However, aerogel fibers generally show weak mechanical properties and complex preparation processes. Herein, through firstly preparing a cellulose acetate/polyacrylic acid (CA/PAA) hollow fiber using coaxial wet-spinning followed by injecting the silk fibroin (SF) solution into the hollow fiber, the CA/PAA-wrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 43 publications
2
40
0
Order By: Relevance
“…The pore size significantly influences the mechanism of heat transfer via thermal conduction. Aerogels contain a gas phase that decreases the amount of collisions between the molecules, thus decreasing the thermal conductivity and limiting convective mass transfer [ 31 , 36 ]. The thermal conductivity decreases with an increase in the density and a decrease in the porosity.…”
Section: Characterization Of the Polysaccharide Aerogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pore size significantly influences the mechanism of heat transfer via thermal conduction. Aerogels contain a gas phase that decreases the amount of collisions between the molecules, thus decreasing the thermal conductivity and limiting convective mass transfer [ 31 , 36 ]. The thermal conductivity decreases with an increase in the density and a decrease in the porosity.…”
Section: Characterization Of the Polysaccharide Aerogelsmentioning
confidence: 99%
“…The density of an aerogel can be as low as 0.004–0.5 g/cm 3 with a high porosity of up to 99.8% and a large specific surface area of 100–1600 m 2 /g [ 11 ]. Due to these properties, the aerogels have been applied as adsorbents of CO 2 [ 12 , 13 , 14 , 15 , 16 ], dyes, and heavy metals [ 2 , 3 , 11 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], as tissue engineering and blood system scaffolds in the biomedical field [ 3 , 22 , 23 , 24 , 25 , 26 , 27 ], and as materials for thermal insulation [ 4 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ] and food packaging [ 37 , 38 , 39 , 40 , 41 ]. These versatile materials also exhibit high optical transparencies, low thermal conductivities (down to 12 mW/mK) and low sound speeds [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…The stress–strain curves of CAFs obtained from tensile tests showed that the breaking stress was in the range of 4.5–5.4 MPa. All the samples showed good tensile strength, which was much higher than that of native silica aerogel fibers, and it was comparable or even superior to those of CA/PAA-SF aerogel fibers [ 41 ] (3 MPa), SF/GO aerogel fibers [ 36 ] (3.2 MPa), and PAO@ANF aerogel fibers [ 28 ] (4.56 MPa). Moreover, the curves also showed that the elongation at break of the sample decreased from 6.8% to 1.1% with increasing precursor concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been found that constructing porous structure is an effective way to reduce the thermal conductivity of fibers [18][19][20][21][22]. On the one hand, the porous structure will lengthen the path of heat transfer and hinder the gaseous heat conduction, leading to a low solid and gas heat transfer [18,19].…”
Section: Introductionmentioning
confidence: 99%